2021
DOI: 10.1213/ane.0000000000005278
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Neurocognitive Disorders After Closed-Loop Versus Manual Target Controlled-Infusion of Propofol and Remifentanil in Patients Undergoing Elective Major Noncardiac Surgery: The Randomized Controlled Postoperative Cognitive Dysfunction-Electroencephalographic-Guided Anesthetic Administration Trial

Abstract: BACKGROUND: The aim of the study was to investigate whether closed-loop compared to manual bispectral index (BIS)–guided target-controlled infusion of propofol and remifentanil could decrease the incidence of postoperative neurocognitive disorders after elective major noncardiac surgery. METHODS: Patients aged >50 admitted for elective major noncardiac surgery were included in a single-blind randomized (ratio 2:1) trial. The anesthetic protocol was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The occurrence of POCD is the result of multifactor synergy. 19 Accumulating studies have demonstrated the important role that anesthesia plays in the occurrence and development of POCD. 20 Anesthetics can activate inositol triphosphate receptors and ryanodine receptors on the endoplasmic reticulum membrane of nerve cells, thereby inducing the pathology and death of neurons.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of POCD is the result of multifactor synergy. 19 Accumulating studies have demonstrated the important role that anesthesia plays in the occurrence and development of POCD. 20 Anesthetics can activate inositol triphosphate receptors and ryanodine receptors on the endoplasmic reticulum membrane of nerve cells, thereby inducing the pathology and death of neurons.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The occurrence of POCD is the result of multifactor synergy . Accumulating studies have demonstrated the important role that anesthesia plays in the occurrence and development of POCD .…”
Section: Resultsmentioning
confidence: 99%
“…Previous study showed RTA-408 protected against propofol-induced cognitive impairment in neonatal mice [ 4 ]. Additionally, repeated propofol exposure could induce neuronal damage and cognitive impairment in aged rats [ 16 ]. Similarly, propofol was successfully used to induce inflammation and apoptosis of hippocampal neurons in rats [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…216,217 Numerous manuscripts on fully automated anesthetic delivery have also been published, 218 from automated general anesthesia 219,220,206 to automated sedation for transcatheter aortic valve replacement, 221 and from simple pilot studies 222 to randomized controlled trials. 223,224 At the same time, Anesthesia & Analgesia has also led the way in publishing articles from US Food and Drug Administration (FDA) authors that delineate the regulatory pathways that need to be passed to make automated anesthesia systems commercially available. 225 Although it is unclear when these systems will be able to enter clinical practice, regulatory barriers have now been identified and discussed extensively.…”
Section: The 1980s and 1990s: Pulse Oximetry Computers And Simulationmentioning
confidence: 99%
“…216,217 Numerous manuscripts on fully automated anesthetic delivery have also been published, 218 from automated general anesthesia 219,220,206 to automated sedation for transcatheter aortic valve replacement, 221 and from simple pilot studies 222 to randomized controlled trials. 223,224…”
Section: To 2022: Automated Anesthesia Advanced Monitors and Artifici...mentioning
confidence: 99%